Kejadian Anemia pada Ibu Hamil: (Studi Analitik di Puskesmas Pertiwi Kota Makassar Provinsi Sulawesi Selatan) - Hariati Hariati; Andi Alim Bagu; Ali Imran Thamrin (Sarana Ilmu Indonesia (salnesia), 2019)
Anemia is caused by the lack number of red blood cells to distribute oxygen to system and fetus, anemia can be known if the content of Hb < 11 mg. The purpose of this research was to find out the relation of nutrition knowledge, food supply, and obedience in consuming Fe tablet with anemia in Pertiwi Health Center South Sulawesi Province. The type of research used was analytical survey with cross sectional design and collected using questionnaire with total samples of 158 people. The result of this research showed that there was relation of knowledge and anemia (p=0,009), there was relation of food supply and anemia (p=0,004), and there is relation of obedience in consuming Fe tablet with anemia (p=0,004). It is suggested to pregnant mother to always pay attention to the fetus by maintaining the food supply and routinely consume Fe tablets during pregnancy, because it affects the fetus health, growth and development.